Owls (Strigiformes) Annotated and Illustrated Checklist - Weick, Friedhelm (Springer Berlin Heidelberg : Imprint: Springer, 2006)
The owl is a magical creature: it exudes an ambivalent fascination that can trigger completely antithetical responses. On the one hand, there is something unsettling about the owl's soundless flight, eerie call, and nocturnal activity that can result in its demonization as a messenger of darkness. On the other hand, however, its masklike visage and seemingly penetrating gaze prove - thralling, and this may have contributed to the deification of the owl as the companion spirit of an omniscient mother earth. In addition, the highly s- cialized captor of prey aroused the competitive envy of hunting parties, even provoking a bit of resentment when they lost out to owls in their hunt for small game. Moreover, the excrement and pellets (hairballs) they deposited in barns and church towers contributed to their reputation as undesirables or even pests. With the overcoming of superstition and suspicion, our relati- ship with these creatures of the night has now become one of unreserved - miration. They grant us insights into the rich diversity of adaptation to n- turnal hunting as well as into sound inventories, brooding biology, and ne- ling development. In a complete transformation of what was once a symbol of fear and hatred, charismatic owls now enjoy an almost singular popularity in large parts of the population.